Pelanggaran Prinsip Kesantunan Berbahasa dalam Kolom Komentar pada Channel Youtube Ferry Irwandi - Rico Ikhsani; Etin Pujihastuti; Vera Krisnawati (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to describe the forms of violations of the principle of linguistic politeness by netizens in a video titled “Exposing the Lies About Black Magic & Indigo Children,” which was released on November 4, 2024. The approach used in this study is qualitative descriptive using the (SBLC) method as well as note-taking to identify, classify, and analyze netizens’ comments on the video titled “Exposing the Lies of Black Magic & Indigo” uploaded on November 4, 2024. The results of the study indicate that all six types of violations of the maxims of politeness according to Leech—namely the maxims of prudence, generosity, praise or appreciation, modesty, agreement, and sympathy—were found in the form of violations, with a total of 60 comments. The most dominant violation was found in the maxim of agreement, with 31 comments; next, violations of the maxim of praise or appreciation were found in 24 comments. Meanwhile, violations of the maxim of prudence were found in 2 comments, while violations of the maxims of generosity, modesty, and sympathy were each found in 1 comment. These findings indicate that in discussions regarding mystical issues on YouTube, netizens tend to disregard the principles of polite language, thus necessitating an increase in awareness of polite language within digital communication spaces. Keywords: Polite language; Violations; YouTube; Mysticism